Pathways Taken by One Canadian College to Advance Reconciliation and the Creation of a New Reconciliation Engagement Program with Indigenous Peoples - Battochio, Randy; Dokis, Andrea; Restoule, Charlene; Restoule, Paige; Mayer, Natasha; Leduc, Mallorie; Roberts, Tana (Engaged Scholar Journal, 2022)
Canada-wide efforts are being made to close the gaps that exist in the health and wellness of Indigenous Peoples besieged by a past of cultural genocide, oppression, and exploitation. The purpose of this essay is to provide members of Colleges and Institutes of Canada (CICan) access to a proposed program to engage in reconciliation, with the objective of facilitating Indigenous community engagement through social innovation, training, and applied research. The proposed program is exemplified through the relationship built between Collège Boréal and Dokis First Nation located in northern Ontario. The proposed Reconciliation Engagement Program consists of two streams that encourage CICan members to utilize, among other possible decolonizing methods, the tenets of a Critical Indigenous Methodology to value and foreground local Indigenous voices. The first stream would consist of networking activities to establish relationships, understand Chief and Council’s vision, and seek opportunities for capacity building within an Indigenous community. The second stream would be project-based so that capital costs and human resources can be accessed to complete each project. While proposing the new program is important, the present essay can also be used to exemplify how Canadian colleges and polytechnics can adopt a decolonizing approach during their engagement with Indigenous communities.